The socio-cultural and anthropological determinants of marriage practice in the region of Msirda - Mortad , Nedjlaà (Journal of Human Sciences, 2023)
This study reveals some major points of the socio-cultural and anthropological aspect of consanguineous marriages in Msirda, let us quote that the part of the parents in the realization of this type of unions is not negligible, moreover, this union seems to be an instrument of strengthening the relationship between the brothers in the region and it is maintained in society despite modernization. The study also shows that among the couples formed there is a significant relationship between the factors studied (level of education, age at first marriage) and consanguineous marriages.